Pengelolaan Program Kerja Komite Sekolah Di Sekolah Dasar Negeri Sibela Timur Jebres Surakarta - Jimin, Jimin; , Prof. Dr. Bambang Sumardjoko; , Dr. Sabar Narimo, MM, M.Pd (2017)
This study aimed to describe: 1) Planning work program committee at East Elementary School Sibela Jebres. 2) Implementation of the program of work of the school committee at East Elementary School Sibela Jebres. 3) evaluation of the work program committee at East Elementary School Sibela Jebres. This research use descriptive research, using descriptive qualitative research design. Implementation of this research is the State Primary School East Sibela Jebres. The research was carried out for six months, since January s / d June 2015. The data used in this study are primary data and secondary data. Sources of data obtained through interview, observation and documentation. As a guest speaker in this study was a teacher, principal and school committee Sibela East State Primary School Jebres. The validity of the data used in this research is triangulation and source triangulation method. Data were analyzed using interactive analysis (model intertwined), which consists of three components: data reduction, data presentation and conclusion. Based on the results of data analysis and discussion we concluded that: 1) Planning work program School Committee in SD Negeri Sibela Eastern Jebres form of assisting the development of RKS, planning in giving feedback to teachers in the implementation of the learning process, the input in the management of infrastructure and planning in supervision of learning activities in schools. 2) Implementation of the work program of the School Committee held with the school committee to implement the planned program to participate in providing input for the preparation of RKS, give input in the implementation of Teaching and Learning, implement programs Management Infrastructures, monitor the implementation of school programs and monitor the results of SLC School , 3) The results of the evaluation of the School Committee Work Program implemented by the school committee to provide input and participate actively endorse RAPBS. In addition to providing input and consideration, the school committee overseeing every budget used by the school.